Implementasi Pendekatan Floor Time untuk Mengatasi Anak Lambat Bicara Usia 3-4 Tahun - Inna Hamida Zusfindhana (Journal of Elementary School (JOES), 2018)
This study examines the implementation of the floor time approach in dealing with children who experience speech delays at 3-4 years old. The floor time approach is one of the therapeutic methods used to overcome speech delays. The purpose of this study is to improve the speech development of children aged 3-4 years. The method used in this research is descriptive qualitative method using observation and interviews to explore children's data with speech delay. Research subjects are children who are slow to talk at 3-4 years old, amounting to one person. The results showed that the ability of children is in the fourth stage, namely complex communication, where children begin to show the phase of incarnation or lalling. The conclusions in this study prove that the floor time approach can help children aged 3-4 years in improving speech development. Keywords : Floortime, Peech Delay, Age 3-4 Years